2017
DOI: 10.1038/srep41283
|View full text |Cite
|
Sign up to set email alerts
|

SWATH label-free proteomics analyses revealed the roles of oxidative stress and antioxidant defensing system in sclerotia formation of Polyporus umbellatus

Abstract: Understanding the initiation and maturing mechanisms is important for rational manipulating sclerotia differentiation and growth from hypha of Polyporus umbellatus. Proteomes in P. umbellatus sclerotia and hyphae at initial, developmental and mature phases were studied. 1391 proteins were identified by nano-liquid chromatograph-mass spectrometry (LC-MS) in Data Dependant Acquisition mode, and 1234 proteins were quantified successfully by Sequential Window Acquisition of all THeoretical fragment ion spectra-MS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 44 publications
(48 reference statements)
1
21
0
Order By: Relevance
“…Differentially expressed proteins contribute to thickened cell wall of sclerotia Proteins in initial sclerotia (IS), development sclerotia (DS) and mature sclerotia (MS) were identi ed by our previous work, so did DEPs of DS vs. IS, MS vs. DS and MS vs. IS 4 . 611 merged DEPs were obtained among the DS vs. IS, MS vs. DS and MS vs. IS groups (as shown in Supplementary Table S1) including 85 unknown proteins (comp11158_c0, comp13970_c0, comp142821_c0, etc) and 526 identi ed proteins (Q49W60, O14241 and Q1K9C2 etc.)…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Differentially expressed proteins contribute to thickened cell wall of sclerotia Proteins in initial sclerotia (IS), development sclerotia (DS) and mature sclerotia (MS) were identi ed by our previous work, so did DEPs of DS vs. IS, MS vs. DS and MS vs. IS 4 . 611 merged DEPs were obtained among the DS vs. IS, MS vs. DS and MS vs. IS groups (as shown in Supplementary Table S1) including 85 unknown proteins (comp11158_c0, comp13970_c0, comp142821_c0, etc) and 526 identi ed proteins (Q49W60, O14241 and Q1K9C2 etc.)…”
Section: Resultsmentioning
confidence: 99%
“…In fact, the medicinal parts of P. umbellatus displayed these bioactivities are a specialized structure named sclerotia which differentiated from hypha 4 . The sclerotium is a structure that supports long-term survival and is intricately linked with structural changes to the thick-walled cell [5][6] induced adverse environmental conditions 7,8 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the integration of complementary approaches and data is mandatory to improve the quality of plant research, and despite all the limitations related to plant organisms, the results reported in the proteomic studies mentioned here are promising and they are attracting the interest of a growing number of plant biologists. In fact, different examples demonstrated the power of high-throughput proteomic technologies to address plant biology questions by characterizing thousands of proteins per sample and multiple biomarkers [ 23 , 25 , 26 , 27 , 28 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, fewer studies relied on the combination of high-throughput proteomic data and protein-protein interaction (PPI) network models [ 20 , 21 , 22 ]. However, in the last few years an increasing number of authors focused their activity on the high-throughput profiling of plant proteomes [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ] as well as on the experimental [ 31 , 32 , 33 ] and computational detection of PPIs [ 34 , 35 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%